1992
DOI: 10.1007/bf00177055
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18 deoxyglucose PET for assessment of viable myocardium in perfusion defects in 99mTc-MIBI SPET: a comparative study in patients with coronary artery disease

Abstract: Extent and frequency of viable tissue in myocardial segments yielding a perfusion defect on technetium-99m methoxyisobutylisonitrile (99mTc-MIBI), single photon emission tomography (SPET) at rest was prospectively investigated with 2-18F-2-deoxyglucose (18FDG) positron emission tomography (PET) in 46 patients with chronic coronary artery disease (CAD). Of these, 43 had a history of old myocardial infarction. For comparative visual and quantitative evaluation of identical anatomical slices, PET image files were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
6

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 24 publications
0
28
0
6
Order By: Relevance
“…nitrogen-13 ammonia, and thus compares perfusion and metabolism of the myocardium [4]. In recent studies technetium-99m sestamibi (MIBI) has been used as a perfusion marker because it shows ideal properties for use in combination with FDG [6,12,13]. It is virtually free from redistribution and its gamma radiation can be easily distinguished from the emission of FDG due to the low gamma-ray energy (140 keV).…”
Section: Methodsmentioning
confidence: 99%
“…nitrogen-13 ammonia, and thus compares perfusion and metabolism of the myocardium [4]. In recent studies technetium-99m sestamibi (MIBI) has been used as a perfusion marker because it shows ideal properties for use in combination with FDG [6,12,13]. It is virtually free from redistribution and its gamma radiation can be easily distinguished from the emission of FDG due to the low gamma-ray energy (140 keV).…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Some showed that the use of a 51% sestamibi threshold, as accepted, with thallium 201 underestimates the extent of viable myocardium. 23,24 By contrast, Udelson et al 22 reported that after rest injection, quantified sestamibi activity paralleled thallium redistribution activity.…”
Section: Predictive Values Of Gated Spect With Different Sestamibi Cumentioning
confidence: 99%
“…The use of technetium-99m ( 99m Tc)-labeled sestamibi, which has been found to have a metabolic impact on myocardial uptake, 14,15 is somewhat controversial. [16][17][18][19][20][21][22][23][24] Several studies have reported that the use of sestamibi leads to an underestimation of the extent of wall motion improvement after revascularization when compared with both thallium 24 and FDG. 23 By contrast, according to others, sestamibi injection under nitrate administration improves viability assessment; this is also true for low-dose dobutamine.…”
Section: Introductionmentioning
confidence: 99%
“…1° But the role of Tc-99m MIBI myocardial SPECT for the identification of myocardial viability is still under investigation." -" Altchoefer et al 6 have demonstrated that Tc99m MIBI at rest underestimated the amount of viable myocardium by 23%. In order to improve the ability to detect myocardial viability by resting Tc-99m MIBI myocardial SPECT, a study of Tc-99m MIBI myocardial SPECT during isosorbide dinitrate (ISDN) infusion was performed in 37 patients with previous myocardial infarction.…”
Section: Introductionmentioning
confidence: 98%